Casting the Account - Hain, H. P. (Journal of Accounting Research, 1967)
The act of counting with is repeatedly mentioned in early texts' as an essential skill of the accountant. Its memory survives in terms and conventions but the once universal practice is almost entirely forgotten. Counting with casters was a form of visual (as distinct from mental) arithmetic which would not only serve for them that cannot read, but also for them that can do both but have not at some time their pen or tables ready with them. 2 It was surprisingly simple and could be practised by the untutored with a minimum of instruction,3 yet lent itself to the complex currency and exchange calculations of Mediaeval business.4 From its beginning the system was associated with the use of Roman numerals5 which are difficultto manipulate directly but can be made